APPLICATION OF ALTERNATIVE TRANSMISSION PIPELINE DURING EMERGENCIES IN INLAND WATER NAVIGATION (Perner's Contacts, 2010)
The paper deals with the influence of the Danube permeability on waterway safety. The next section addresses the possibility of using the alternative pipeline to address the emergency and the transfer of hazardous substances from a tank vessel dedlocked in the fairway.
Keywords: Safety; emergency; pipeline; tank vessel; deadlocked